(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores the intricate relationship between nature and human existence in Thomas Hardy’s Tess of the d’Urbervilles. Hardy’s profound portrayal of the natural world serves as both a reflection and a catalyst of Tess’s life journey. Nature is not merely a backdrop but an active participant in the narrative, influencing and reflecting Tess’s emotions, struggles, and ultimate fate. Through an analysis of the novel’s symbolism, descriptive imagery, and thematic interplay between nature and society, this study highlights the dual role of nature as a source of solace and conflict. Tess’s profound connection to the natural world underscores the harmony and tension that define human existence. Furthermore, Hardy’s critique of societal morality and industrialization, juxtaposed with his reverence for nature’s beauty and power, reveals a deep philosophical inquiry into humanity’s place within the natural order. The analysis underscores the tragic inevitability of Tess’s fate in a world where nature and society remain in constant tension, offering timeless insights into the fragile balance between human aspirations and the inexorable forces of the natural world.